A multilocus sequencing approach reveals the cryptic phylogeographical history of Phyllodoce nipponica Makino (Ericaceae). (14th June 2013) - Ikeda, Hajime; Setoguchi, Hiroaki
Abstract : Discordant phylogeographical patterns among species with similar distributions may not only denote specific biogeographical histories of different species, but also could represent stochastic variance of genealogies in applied genetic markers. A multilocus investigation representing different genomes can be used to address the latter concern, allowing robust inference to biogeographical history. In the present study, we conducted a multilocus phylogeographical analysis to re‐examine the genetic structuring of Phyllodoce nipponica, in which chloroplast (cp)DNA markers exhibited a discordant pattern compared to those of other alpine plants. The geographical structure of sequence variation at five nuclear loci was not consistent with that of cpDNA and showed differentiation between the northern and southern parts of the range of this species. Its demographic history inferred from the isolation‐with‐migration model suggests that the north–south divergence originated from Pleistocene vicariance. In addition, the demographic parameters showed a lack of chloroplast‐specific gene flow, suggesting that stochastic variance in genealogy resulted in the discordant geographical structure. Thus, P. nipponica probably experienced Pleistocene vicariance between its southern and northern range parts in concordance with other alpine plants in the Japanese archipelago. The findings of the present study demonstrates the importance of using a multilocus approach for inferring population dynamics, as well as for reconciling discordant phylogeographical patterns among species. © 2013 The Linnean Society of London, Biological Journal of the Linnean Society, 2013, 110, 214–226.